Phosphate-based low dielectric LTCC (Low Temperature Co-Fired Ceramic) material and preparation method thereof

By adopting Na2O-AO-MgO-xP2O5 chemical expression phosphate-based low-mediated LTCC material, the problem of insufficient sintering temperature and dielectric loss of existing materials is solved, and a low-cost and high-performance microwave dielectric ceramic material preparation is realized, which is suitable for microwave signal transmission in high-frequency circuits.

CN119528561AActive Publication Date: 2025-02-28NANJING INST OF TECH

Patent Information

Application Number
CN202411481716.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-28
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing phosphate microwave dielectric ceramic materials have shortcomings in sintering temperature and dielectric loss, which are difficult to meet the needs of miniaturization and cost reduction of high-frequency circuits.

Method used

Phosphate-based low-intermediate LTCC material with chemical expression of Na2O-AO-MgO-xP2O5 (A=Sr, Ca or Sr1-yCay, 1.0≤x≤1.2, 0

Benefits of technology

The sintering temperature of phosphate-based low-intermediate LTCC materials is significantly reduced, so that their sintering temperature is lowered below 900°C, and the dielectric constant and Q value are within a suitable range, making it suitable for microwave signal transmission in high-frequency communication.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528561A_ABST
    Figure CN119528561A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphate-based low-dielectric LTCC (Low Temperature Co-Fired Ceramic) material and a preparation method thereof, the chemical expression of the phosphate-based low-dielectric LTCC material is Na2O-AO-MgO-xP2O5, A = Sr, Ca or Sr1-yCay, x is more than or equal to 1.0 and less than or equal to 1.2, and y is more than 0 and less than or equal to 0.2. The preparation process sequentially comprises the following steps: synthesizing LTCC ceramic powder, ball-milling, pressing and forming, and sintering to obtain the ceramic. The main crystal phase of the phosphate-based low dielectric LTCC material is Na2MMg (PO4) 2 (A = Sr, Ca or Sr1-yCay), and the phosphate-based low dielectric LTCC material has the advantages of low raw material cost, low sintering temperature (750-900 DEG C), low dielectric constant (8.2-9.3), high Qf value (41800-80310 GHz), simple preparation process, good reproducibility and the like, can solve the time delay problem of microwave signals in high-frequency communication, improves the stability of microwave signal transmission, and has good application prospects. The material is very suitable for being used as an LTCC microwave substrate, a dielectric antenna and other systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of microwave dielectric ceramics, and in particular relates to a phosphate-based low-dielectric LTCC material and a preparation method thereof. Background Art

[0002] As a high-performance material, low-temperature co-fired ceramics (LTCC) have shown extensive application potential in the modern electronics industry. Its low dielectric constant, low loss, high thermal conductivity and good thermal expansion coefficient matching meet the needs of high-frequency, high-speed and highly integrated electronic components such as 5G and the Internet of Things. With the improvement of miniaturization, high performance and reliability requirements, LTCC ceramics play an important role in communications, automotive electronics, aerospace and medical fields, such as manufacturing filters, couplers, automotive electronic control modules, pacemakers and other key components. In the future, with the continuous advancement of technology and the continuous development of the market, the application prospects of LTCC ceramics will be broader.

[0003] Phosphate microwave dielectric ceramics are a type of ceramic material with excellent microwave dielectric properties. They usually have low cost, low sintering temperature, low dielectric constant and low dielectric loss, making them ideal candidate materials in the field of low-temperature co-fired ceramics (LTCC) technology, and provide a solid material foundation for the miniaturization and integration of high-frequency circuits. As 5G technology moves from theory to practical application, how to reduce costs without sacrificing performance has become the key. Therefore, exploring new phosphate systems and optimizing materials and preparation processes are crucial to promoting the development of communication technology and the upgrading of the electronic information industry. The present invention discloses a phosphate-based low-dielectric LTCC material and a preparation method thereof. The ceramic forming temperature of the compound is lower than 950°C and the dielectric loss is low, which is very suitable for use as a microwave dielectric substrate. Summary of the invention

[0004] The object of the present invention is to provide a phosphate-based low dielectric constant LTCC material and a preparation method thereof, wherein the main crystal phase of the material is Na2MMg(PO4)2 ( A =Sr, Ca or Sr 1-y Ca y ), which has the advantages of low cost, low sintering temperature, low dielectric constant, low dielectric loss and stable preparation process.

[0005] In order to solve the problems of the prior art, the present invention provides a phosphate-based low dielectric constant LTCC material, the chemical expression of which is Na2O- A O-MgO- x P2O5, among which A =Sr, Ca or Sr 1-y Ca y , 1.0≤ x ≤1.2,0< y≤0.2.

[0006] The present invention also provides a method for preparing the above-mentioned phosphate-based low-k LTCC material, comprising the following steps: Step 1: Synthesis of LTCC ceramic powder: Using Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 high-purity powders as raw materials, LTCC ceramic powder is prepared by a hydrothermal method or a solid phase sintering method.

[0007] Step 2, ball milling: transfer the synthesized LTCC ceramic powder to a nylon ball mill, add ball milling media and grinding balls, and place it in a planetary ball mill for wet grinding. The grinding balls are made of zirconium dioxide, and the mass ratio of the mixture, grinding balls and ball milling media is 1:5:1.2. The ball milling time is 8-12 hours, and the ball mill speed is 250-350 rpm. Step 3: Pressing and forming: After drying the ball mill slurry, add 5-8 wt% of the weight of the binder, mix, sieve and granulate; press into a green body on a unidirectional press at a pressure of 100-150 MPa; Step 4: Sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and slowly heat it up to 500°C, keep it warm for 2 hours, then heat it up to 650°C, keep it warm for 2 hours, then heat it up to 750~900°C, keep it warm for 4~8 hours, and finally cool it with the furnace to obtain a phosphate-based low-dielectric LTCC material.

[0008] Preferably, the chemical expression of the main crystalline phase of the LTCC material is Na2MMg(PO4)2 ( A =Sr, Ca or Sr 1- y Ca y ).

[0009] Preferably, in step 1, the particle size of the Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 powders is 1-5 μm, and the purity is ≥99.5%.

[0010] Preferably, the specific method for preparing LTCC ceramic powder by hydrothermal method in step 1 is: Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 raw material powders are mixed according to the chemical formula of Na2O- A O-MgO- x P2O5( A =Sr, Ca or Sr 1-y Ca y , 1.0≤ x ≤1.2,0< y≤0.2) to weigh ingredients to form a mixed powder; dissolve the mixed powder in deionized water, then add anhydrous ethanol and a surfactant to the mixed solution and stir to form a turbid liquid, transfer the turbid liquid to a high-pressure reactor, gradually heat it to 120-150°C to react for 12-24 hours, cool it to room temperature, wash it three times by circulating centrifugation with deionized water and anhydrous ethanol, and dry it at 90°C for 4 hours to obtain LTCC ceramic powder.

[0011] Preferably, the specific method for preparing LTCC ceramic powder by solid phase sintering in step 1 is: Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 raw material powders are sintered according to the chemical formula of Na2O- A O-MgO- x P2O5( A =Sr, Ca or Sr 1- y Ca y , 1.0≤ x ≤1.2,0< y ≤0.2) to weigh and mix the ingredients to form a mixed powder; transfer the mixed powder to an alumina crucible, put it into a box-type resistance furnace, heat it to 600~700℃, keep it warm for 4~6h, and then cool it to room temperature.

[0012] Preferably, the ball milling medium is anhydrous ethanol or deionized water.

[0013] Preferably, the adhesive is a polyvinyl alcohol aqueous solution with a concentration of 5 wt %.

[0014] Preferably, the mixed powder is dissolved in deionized water to prepare a mixed solution with a mass concentration of 10%; then anhydrous ethanol and a surfactant are added to the mixed solution, wherein the anhydrous ethanol accounts for 30% of the total volume of the mixed solution and the surfactant accounts for 10% of the total volume of the mixed solution.

[0015] Preferably, the surfactant is one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide and a silane coupling agent.

[0016] The present invention has the beneficial effects: (1) The present invention utilizes excess phosphorus to solve the problem of the existence of a second phase in phosphate ceramics in traditional solid phase synthesis, and can also significantly reduce the sintering temperature of phosphate-based low-k LTCC materials, reducing their sintering temperature to below 900°C, and can be applied in the LTCC field.

[0017] (2) The sintering temperature of the phosphate-based low-dielectric LTCC material prepared by the present invention is 750-900°C, the dielectric constant is 8.2-9.3, and Q fThe value is 41800~80310GHz, which can solve the delay problem of microwave signals in high-frequency communications and improve the stability of microwave signal transmission. It is very suitable for use as LTCC microwave substrates, dielectric antennas and other systems.

[0018] (3) The phosphate-based low-k LTCC material provided by the present invention has a simple preparation process, low raw material cost, no pollution to the environment, and good production process stability, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the XRD spectrum of the phosphate-based low-k LTCC material prepared in Example 1 of the present invention.

[0020] Figure 2 This is a SEM image of the phosphate-based low-k LTCC material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described below. The following examples are only used to more clearly illustrate the technical solution of the present invention, and are not intended to limit the protection scope of the present invention.

[0022] Table 1 shows the mixed powders of five ingredients. Phosphate-based low dielectric LTCC materials were prepared by using different process parameters, and their microwave dielectric properties were measured respectively.

[0023] Table 1 Mixture of five ingredients (mol%) Element <![CDATA[Na2CO3]]> <![CDATA[SrCO3]]> <![CDATA[CaCO3]]> <![CDATA[Mg(OH)2]]> <![CDATA[NH4H2PO4]]> <![CDATA[1 # ]]> 1 1 0 1 2 <![CDATA[2 # ]]> 1 0 1 1 2 <![CDATA[3 # ]]> 1 0.9 0.1 1 2 <![CDATA[4 # ]]> 1 1 0 1 2.4 <![CDATA[5 # ]]> 1 0 1 1 2.2 Embodiment 1

[0024] Step 1, LTCC ceramic powder synthesis: Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 raw material powders are weighed and mixed according to the ingredient formula in Table 1 to form a mixed powder; the mixed powder is dissolved in deionized water to prepare a mixed solution with a mass concentration of 10%; then anhydrous ethanol and sodium dodecyl sulfate are added to the mixed solution and stirred to form a turbid solution, wherein anhydrous ethanol accounts for 30% of the total volume of the mixed solution, and the surfactant accounts for 10% of the total volume of the mixed solution; the turbid solution is transferred to a high-pressure reactor, gradually heated to 120°C for reaction for 24h, cooled to room temperature, and washed three times by centrifugation with deionized water and anhydrous ethanol, and dried at 90°C for 4h to obtain LTCC ceramic powder.

[0025] Step 2, ball milling: the synthesized LTCC ceramic powder is transferred to a nylon ball mill, ball milling medium and grinding balls are added, and the mixture is wet milled in a planetary ball mill. The ball milling medium is deionized water, the grinding balls are made of zirconium dioxide, the mass ratio of the mixture, the grinding balls and the deionized water is 1:5:1.2, the ball milling time is 12 hours, and the ball mill speed is 250 rpm; Step 3: Pressing and forming: After drying the ball mill slurry, add 8 wt% of the weight of the binder, mix, sieve and granulate; press into a green body at a pressure of 150 MPa on a unidirectional press; Step 4: Sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and slowly heat it to 500°C, keep it warm for 2 hours, then heat it to 650°C, keep it warm for 2 hours, then heat it to 750°C, keep it warm for 8 hours, and finally cool it with the furnace to obtain a phosphate-based low-dielectric LTCC material.

[0026] The performance of the material obtained in this example was tested, and the test results are shown in Table 2.

[0027] Table 2 Dielectric properties of different materials prepared using Example 1 Element <![CDATA[1 # ]]> <![CDATA[2 # ]]> <![CDATA[3 # ]]> <![CDATA[4 # ]]> <![CDATA[5 # ]]> Dielectric constant 9.20 8.82 9.22 9.05 8.77 Q value (GHz) 68370 54680 78500 65110 61370 <![CDATA[ τ f (ppm / ℃)]]> -54.8 -44.0 -58.4 -52.9 -45.5 Embodiment 2

[0028] Step 1, LTCC ceramic powder synthesis: Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 raw material powders are weighed and mixed according to the ingredient formula in Table 1 to form a mixed powder; the mixed powder is dissolved in deionized water to prepare a mixed solution with a mass concentration of 10%; then anhydrous ethanol and sodium dodecyl sulfate are added to the mixed solution and stirred to form a turbid solution, wherein anhydrous ethanol accounts for 30% of the total volume of the mixed solution, and the surfactant accounts for 10% of the total volume of the mixed solution; the turbid solution is transferred to a high-pressure reactor, gradually heated to 150°C for reaction for 12 hours, cooled to room temperature, and washed three times by centrifugation with deionized water and anhydrous ethanol, and dried at 90°C for 4 hours to obtain LTCC ceramic powder.

[0029] Step 2, ball milling: the synthesized LTCC ceramic powder is transferred to a nylon ball mill, ball milling medium and grinding balls are added, and the mixture is wet-milled in a planetary ball mill. The ball milling medium is anhydrous ethanol, the grinding balls are made of zirconium dioxide, the mass ratio of the mixture, the grinding balls and anhydrous ethanol is 1:5:1.2, the ball milling time is 8 hours, and the ball mill speed is 350 rpm; Step 3, pressing and molding: after drying the ball mill slurry, add 5wt% of the weight of the slurry and a 5wt% polyvinyl alcohol aqueous solution, mix, sieve and granulate; press into a green body at a pressure of 100MPa on a unidirectional press; Step 4: Sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and heat it slowly to 500°C, keep it warm for 2 hours, then heat it to 650°C, keep it warm for 2 hours, then heat it to 850°C, keep it warm for 4 hours, and finally cool it with the furnace to obtain a phosphate-based low-dielectric LTCC material.

[0030] The performance of the material obtained in this example was tested, and the test results are shown in Table 3.

[0031] Table 3 Dielectric properties of different materials prepared using Example 2 Element <![CDATA[1 # ]]> <![CDATA[2 # ]]> <![CDATA[3 # ]]> <![CDATA[4 # ]]> <![CDATA[5 # ]]> Dielectric constant 8.92 8.25 8.68 8.73 8.55 Q value (GHz) 57500 42510 76780 51530 48920 <![CDATA[ τ f (ppm / ℃)]]> -46.8 -45.6 -55.5 -54.0 -47.8 Embodiment 3

[0032] Step 1, LTCC porcelain powder synthesis: Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 raw material powders are weighed and mixed according to the ingredient formula in Table 1 to form a mixed powder, the mixed powder is transferred to an alumina crucible, placed in a box-type resistance furnace, heated to 600°C, kept warm for 6 hours, and then cooled to room temperature.

[0033] Step 2, ball milling: the synthesized LTCC ceramic powder is transferred to a nylon ball mill, ball milling medium and grinding balls are added, and the mixture is wet milled in a planetary ball mill. The ball milling medium is deionized water, the grinding balls are made of zirconium dioxide, the mass ratio of the mixture, the grinding balls and the deionized water is 1:5:1.2, the ball milling time is 12 hours, and the ball mill speed is 250 rpm; Step 3: Pressing and forming: After drying the ball mill slurry, add 8 wt% of the weight of the binder, mix, sieve and granulate; press into a green body at a pressure of 150 MPa on a unidirectional press; Step 4: Sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and slowly heat it to 500°C, keep it warm for 2 hours, then heat it to 650°C, keep it warm for 2 hours, then heat it to 800°C, keep it warm for 7 hours, and finally cool it with the furnace to obtain a phosphate-based low-dielectric LTCC material.

[0034] The performance of the material obtained in this example was tested, and the test results are shown in Table 4.

[0035] Table 4 Dielectric properties of different materials prepared using Example 3 Element <![CDATA[1 # ]]> <![CDATA[2 # ]]> <![CDATA[3 # ]]> <![CDATA[4 # ]]> <![CDATA[5 # ]]> Dielectric constant 9.12 8.47 9.02 9.05 8.41 Q value (GHz) 55620 41800 65580 47880 42330 <![CDATA[ τ f (ppm / ℃)]]> -55.0 -52.5 -51.1 -49.8 -47.5 Embodiment 4

[0036] Step 1: Synthesis of LTCC ceramic powder: weigh and mix the raw material powders of Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 according to the composition formula in Table 1 to form a mixed powder, transfer the mixed powder into an alumina crucible, place it in a box-type resistance furnace, heat it to 700°C, keep it warm for 4 hours, and then cool it to room temperature.

[0037] Step 2, ball milling: the synthesized LTCC ceramic powder is transferred to a nylon ball mill, ball milling media and grinding balls are added, and the mixture is wet-milled in a planetary ball mill. The ball milling medium is anhydrous ethanol, the grinding balls are made of zirconium dioxide, the mass ratio of the mixture, the grinding balls and anhydrous ethanol is 1:5:1.2, the ball milling time is 10 hours, and the ball mill speed is 300 rpm; Step 3, pressing and molding: After drying the ball mill slurry, add 7wt% of its weight and 5wt% polyvinyl alcohol aqueous solution, mix, sieve and granulate; press into a green body on a uniaxial press at a pressure of 120MPa; Step 4: Sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and heat it slowly to 500°C, keep it warm for 2 hours, then heat it to 650°C, keep it warm for 2 hours, then heat it to 900°C, keep it warm for 5 hours, and finally cool it with the furnace to obtain a phosphate-based low-dielectric LTCC material.

[0038] The performance of the material obtained in this example was tested, and the test results are shown in Table 5.

[0039] Table 5 Dielectric properties of different materials prepared using Example 4 Element <![CDATA[1 # ]]> <![CDATA[2 # ]]> <![CDATA[3 # ]]> <![CDATA[4 # ]]> <![CDATA[5 # ]]> Dielectric constant 9.30 8.64 9.15 9.17 8.59 Q value (GHz) 68100 51900 80310 65440 51220 <![CDATA[ τ f (ppm / ℃)]]> -48.2 -48.0 -53.8 -57.2 -50.2 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a phosphate-based low dielectric constant LTCC material, characterized in that: The chemical expression of the LTCC material is Na2O- A O-MgO- x P2O5, among which A =Sr, Ca or Sr 1-y Ca y , 1.0≤ x ≤1.2,0< y ≤0.2; The method for preparing the phosphate-based low dielectric constant LTCC material comprises the following steps: Step 1, LTCC ceramic powder synthesis: using Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 high-purity powder as raw materials, LTCC ceramic powder is prepared by hydrothermal method or solid phase sintering method; Step 2, ball milling: transfer the synthesized LTCC ceramic powder to a nylon ball mill, add ball milling media and grinding balls, and place it in a planetary ball mill for wet grinding. The grinding balls are made of zirconium dioxide, and the mass ratio of the mixture, grinding balls and ball milling media is 1:5:1.

2. The ball milling time is 8-12 hours, and the ball mill speed is 250-350 rpm. Step 3: Pressing and forming: After drying the ball mill slurry, add 5-8 wt% of the weight of the binder, mix, sieve and granulate; press into a green body on a unidirectional press at a pressure of 100-150 MPa; Step 4: Sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and slowly heat it up to 500°C, keep it warm for 2 hours, then heat it up to 650°C, keep it warm for 2 hours, then heat it up to 750~900°C, keep it warm for 4~8 hours, and finally cool it with the furnace to obtain a phosphate-based low-dielectric LTCC material.

2. The method for preparing a phosphate-based low-k LTCC material according to claim 1, characterized in that: The chemical expression of the main crystalline phase of the LTCC material is Na2MMg(PO4)2( A =Sr, Ca or Sr 1-y Ca y ).

3. The method for preparing a phosphate-based low-k LTCC material according to claim 1, characterized in that: In step 1, the particle size of Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 powders is 1~5μm, and the purity is ≥99.5%.

4. The method for preparing a phosphate-based low-k LTCC material according to claim 1, characterized in that: The specific method for preparing LTCC ceramic powder by hydrothermal method in step 1 is: Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 raw material powders are mixed according to the chemical formula of Na2O- A O-MgO- x P2O5( A =Sr, Ca or Sr 1-y Ca y , 1.0≤ x ≤1.2,0< y ≤0.2) to weigh ingredients to form a mixed powder; dissolve the mixed powder in deionized water, then add anhydrous ethanol and a surfactant to the mixed solution and stir to form a turbid liquid, transfer the turbid liquid to a high-pressure reactor, gradually heat it to 120-150°C to react for 12-24 hours, cool it to room temperature, wash it three times by circulating centrifugation with deionized water and anhydrous ethanol, and dry it at 90°C for 4 hours to obtain LTCC ceramic powder.

5. The method for preparing a phosphate-based low-k LTCC material according to claim 1, characterized in that: The specific method for preparing LTCC ceramic powder by solid phase sintering in step 1 is: Na2CO3, SrCO3, CaCO3, Mg(OH)2 and NH4H2PO4 raw material powders are sintered according to the chemical formula of Na2O- A O-MgO- x P2O5( A =Sr, Ca or Sr 1-y Ca y , 1.0≤ x ≤1.2,0< y ≤0.2) to weigh and mix the ingredients to form a mixed powder; transfer the mixed powder to an alumina crucible, put it into a box-type resistance furnace, heat it to 600~700℃, keep it warm for 4~6h, and then cool it to room temperature.

6. The method for preparing a phosphate-based low-k LTCC material according to claim 1, characterized in that: The ball milling medium is anhydrous ethanol or deionized water.

7. The method for preparing a phosphate-based low-k LTCC material according to claim 1, characterized in that: The adhesive is a polyvinyl alcohol aqueous solution with a concentration of 5wt%.

8. The method for preparing a phosphate-based low dielectric constant LTCC material according to claim 4, characterized in that: The mixed powder is dissolved in deionized water to prepare a mixed solution with a mass concentration of 10%; then anhydrous ethanol and a surfactant are added to the mixed solution, wherein the anhydrous ethanol accounts for 30% of the total volume of the mixed solution and the surfactant accounts for 10% of the total volume of the mixed solution.

9. The method for preparing a phosphate-based low-k LTCC material according to claim 4, characterized in that: The surfactant is one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide and a silane coupling agent.

Citation Information

Patent Citations

  • A low-temperature co-fired ceramic material and a preparing method thereof

    CN106032318A

  • Low-dielectric low temperature co-fired ceramic material and preparation method thereof

    CN109734428A

  • Low dielectric and low loss boride LTCC material and preparation method thereof

    CN114180939A

Cited By

  • Pyrophosphate microwave dielectric ceramic material for LTCC (Low Temperature Co-Fired Ceramic) and preparation method thereof

    CN121318429A